The Effectiveness of Cooperative Learning with STAD Technique to Improve Writing Skill and Motivation of English Department Students in UKI Toraja - Sushy Sushy (UKI TORAJA, 2016)
This research aimed to find out whether the Cooperative Learning with STAD technique improves the students’ writing skill of English Department students at UKI Toraja. The other objective is whether the students are motivated to the use of STAD.This research employed quasi-experimental design. It used two groups, one received STAD technique, Cooperative Learning method treatment and the other group received Group Learning method. The subjects of this research were class D and E of sixth semester student in academic year 2012/2013. Each group consists of 21 students. The data of this research was collected through writing test and questionnaire.The results of the research revealed that (1) the use of Cooperative Learning with STAD Technique improved the writing achievement of the sixth semester students from class D in experimental class. It is similar to the use of Group Learning in control group, but the improvement is more significant by using the Cooperative Learning with STAD Technique. It is shown by the mean score of pre-test and post-test. In control group the mean score increased from 63.05 to 69.95, while in experimental group the score increased from 58.24 to 79.4 (2) the students had high motivation in learning writing by using Cooperative Learning with STAD Technique. It was proved by the mean score of questionnaire, 83.05 which classified into motivated category.